2023
DOI: 10.3390/su151411417
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Humic Acids in Drained Floodplain Soils in Temperate Climates: A Spectroscopic Study

Abstract: This study aims to assess the characteristics of humic acids (HAs) in floodplain soils. HAs were isolated from the Fluvisols located out of the embankment in the riparian forest (unflooded riparian forest) and within the embankment (inter-embankment), in the area periodically flooded. HAs from these soils were examined for quantity, structure, and humification degree using extraction methods as well as elemental analysis, UV-Vis, FTIR, EPR, and 1HNMR spectroscopies. In the soils after drainage, a significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Therefore, it can be concluded that the peaks in this region corresponded to the extractant that was used for the isolation of HSs. The second area, which was not considered in the analysis of spectra, was the region of 4.3–6.0 ppm, characteristic of the D 2 O shift, which was used as a solvent in the analysis of humic extracts. , In the remaining resonance areas, three signals that may be assigned to the molecular structures of HSs were observed. The first one (A), which was peaking below 1.6 ppm, corresponds to the protons of methyl and methylene groups in aliphatic structures .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be concluded that the peaks in this region corresponded to the extractant that was used for the isolation of HSs. The second area, which was not considered in the analysis of spectra, was the region of 4.3–6.0 ppm, characteristic of the D 2 O shift, which was used as a solvent in the analysis of humic extracts. , In the remaining resonance areas, three signals that may be assigned to the molecular structures of HSs were observed. The first one (A), which was peaking below 1.6 ppm, corresponds to the protons of methyl and methylene groups in aliphatic structures .…”
Section: Resultsmentioning
confidence: 99%